Aquisição fonológica atípica do português brasileiro : evidências sobre complexidade dos sistemas fonológicos de crianças com desvio fonológico - Henrich, Vanessa (2013)
This research has a sample of 111 phonological inventories of children with phonological deviation. It intended to verify if all hypothesis of Modelo Implicacional de Complexidade de Traços MICT (MOTA, 1996) have confirmed themselves, they way they are supposed to. It is a quantitative study of descriptive cross-sectional type, in which the data was analysed statistically by Statistical Package for Social Sciences (SPSS) program. This research deals only with consonant acquirement. At the first moment it verified the segment status in each phonological inventory, if they were acquired, being acquired or absent. Done that, a comparison was established between the results of this sample and the results of Mota (1996) sample. The study verified that the general expectations of MICT were confirmed, with an exception of rhotic consonant order acquirement. The vibrant, executed as fricative, or [x], emerges early than the tap, differently than what MICT predicted. However, it was observed that the children who are still acquiring the vibrant, a lot of times replace it for a liquid or a glide, what suggests that even when pronounced as a fricative, it seems like an allophone of the vibrant. Another divergent occurrences were found and constitute only expected variations